Reseñas bibliográficas (1984)
BEITRÄGE ZUM VIII. GEOWISSENSCHATLICHEN LATEINAMERKA -KOLLOQUIUM. GÖTTINGEN 1982.-Zentralblatt für Geologie und Paläontologie, Parte I, número 314. Editado por H. Miller and amp; Rosenfeld, E. Schewizerbart'sche Velagsburchhandlung (Nägele U. Obermiller), Stuttgart, 1983. / ZEIL, W. (1983): Das präkambrische Basament der Anden. Ein Überlick. The precambrian Basement of the Andes. A Review.-Zbl. Geol. Paläont, Teil 1, H. 3/4, pp. 246-254, Stuttgart. / OCHSENIUS, C. (1983): Aridity and Biogeography in Northermost South America During the Late Pleistocene (Peri-Caribbean Arid Belt, 62°-74°W).-Zbl. Geo. Paläont. Teil I,H. 3/4, pp. 264-278, Stuttgart. / MOJICA, J. MACIA, C. (1983): Über die Stratigraphie und Altersstellung der Yavi-Formation im oberen Magdalena Tal, Tolirna Kolumbien.·Zbl. Geol. Palaont. Teil I, H. 3/4, pp. 279-290, Stuttgart. / FLÜH, E. R. (1983): The Basic Igneous Complex. Trace of an Ancient Galápagos Hot Spot Aseismic Ridge?· Zbl. Geol. Paläont, Teil 1, H. 3/4, pp. 241-303, Stuttgart. / ACOSTA, C. E. (1983): Geodynamics of Ecuador.-Geodynamics of Eastern Pacific Region, Caribbean and Scotia Arcs.·Geodynamic Series v. 9, pp. 53·63, American Geophysical Union. / GALVIS, J. (1980): Un Arco de Islas Terciario en el Occidente Colombiano.- Geol. Colomb. No. 11, pp. 7·43, Bogotá. / HALL, M. (1983): El origen subaéreo de la Isla Española y la edad de la vida terrestre, Islas Galápagos.- Politécnica, Monografía de Geología 3, v. VIII, No.2, pp. 7-35, Quito. / MURCIA, L. A. (1980): Definición del denominado Complejo Igneo Básico en Colombia y Patogénesis de su parte meridional.· Geol. Colomb. No. 11, pp. 45-65, Bogotá. / SCHMITT, C. (1983): Junger Vulkanismus in den Kordillerenzügen Südkolumbiens.- Zbl. Geol. Paläont. Teil I, H, 3/4, pp. 318-328, Stuttgart. / LÜSCHEN, E. (1983): Recent Tectonics of the Northern Andes According to Geophysical and Geodetical Measurements in Colombia.- Zbl. Geol. Paläont. Teil I, H. 3/4, pp. 304·317, Stuttgart. / TAKEMURA, K. and amp; DANHARA, T. (1983): Fission-Track Age of Pumices included in the Gigante Formation, North of Neiva, Colombia-Report of New World Monkeys, III, 13-16. Kyoto University Primate Research Institute, Kyoto. / TAKEMURA, K. (1983): Geology of the East Side Hills of the Rio Magdalena from Neiva to Villavieja, Colombia.- Report of New World Monkeys, III, 19-28. Kyoto University Primate Research Institute, Kyoto. / SETOGUCHI, T. and amp; CADENA, A. (1984): Relación entre la Morfología y la función de la Dentura en el Linaje Stirtonia-Alouatta (Ceboidea).· Report of New World Monkeys, IV. 11-20. Kyoto University Primate Research Institute, Kyoto. / HAYASHIDA, A. (19841: Paleomagnetic Study of the Miocene Continental Deposits in La Venta Badlands, Colombia- Report of New World Monkeys, IV, 77-83. Kyoto University Primate Research Institute, Kyoto. / KOLLA, V., BUFFLER, R. T. and amp; LADD, J. (1984): Seismic Stratigraphy and Sedimentation of Magdalena Fan, Southern Colombian Basin, Caribbean Sea.- Am. Assoc. Petrol. Geol. Bull. 68 (3), p. 316-332.